RADI-16. ECONOMIC IMPLICATIONS OF PREOPERATIVE VERSUS POSTOPERATIVE STEREOTACTIC RADIOSURGERY FOR BRAIN METASTASES. (12th August 2019) - Ward, Matthew; Prabhu, Roshan; Asher, Anthony; Wait, Scott; Sumrall, Ashley; Shah, Chirag; Burri, Stuart
Abstract: OBJECTIVE: Retrospective data suggests preoperative stereotactic radiosurgery (preSRS) reduces radiation necrosis (RN) and leptomeningeal disease (LMD) failure after resection of brain metastases (BM) as compared to postoperative SRS (postSRS). We evaluated the potential financial impact of a reduction in symptomatic RN (SRN) and LMD, should preSRS become a national standard. METHODS: A decision tree was designed to evaluate the two strategies: preSRS vs. postSRS. We assumed no difference in survival and that a reduction in SRN and LMD exists on par with retrospective data. Effectiveness was not considered given unclear health utilities. Treatments for SRN considered were dexamethasone, bevacizumab, surgical resection, or hyperbaric oxygen (HBO). Treatments for LMD considered included conventional radiation, SRS, systemic therapy (lapatinib/capecitabine), or no therapy. Probabilities were extracted from the 2-year LMD/SRN rates and subsequent treatment patterns observed in retrospective data. Treatment costs were based on the 2019 Medicare physician fee schedule and published data in 2019 US dollars without discounting. National costs to the healthcare system were estimated by assuming 200, 000 BM cases per year with a surgical utilization rate of 16%. Deterministic and probabilistic sensitivity analyses (PSA) were performed. RESULTS: The incorporated rate of LMD and SRN for postSRS was 22.4% and 16.4% and 4.3% and 4.9% for preSRS, respectively. The expected mean costs were $3, 129 for postSRS and $810 for preSRS. Deterministic sensitivity analysis demonstrated that the model was sensitive to only LMD/SRN rates. PSA demonstrated that in 95% of simulations, the expected savings ranged from $770-$6, 429/patient. Therefore, the national healthcare system stands to save approximately $74 million per year if preSRS was a national standard (range $25–206 million). CONCLUSIONS: A prospective randomized trial demonstrating the effectiveness of preSRS in the reduction of LMD and/or SRN would carry a significant return on investment through the reduction of subsequent treatment costs.